2019
DOI: 10.1038/s41398-018-0348-7
|View full text |Cite
|
Sign up to set email alerts
|

Fetal glucocorticoid receptor (Nr3c1) deficiency alters the landscape of DNA methylation of murine placenta in a sex-dependent manner and is associated to anxiety-like behavior in adulthood

Abstract: Prenatal stress defines long-term phenotypes through epigenetic programming of the offspring. These effects are potentially mediated by glucocorticoid release and by sex. We hypothesized that the glucocorticoid receptor (Gr, Nr3c1) fashions the DNA methylation profile of offspring. Consistent with this hypothesis, fetal Nr3c1 heterozygosity leads to altered DNA methylation landscape in fetal placenta in a sex-specific manner. There was a significant overlap of differentially methylated genes in fetal placenta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…Table S1. High-throughput studies analyzing methylation profiles of different relevant tissues in the context of preeclampsia [42,43,47,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73].…”
mentioning
confidence: 99%
“…Table S1. High-throughput studies analyzing methylation profiles of different relevant tissues in the context of preeclampsia [42,43,47,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73].…”
mentioning
confidence: 99%
“…In that sense, it could be possible that glucocorticoid receptor expression may be promoted after mating for the upcoming events. Previous studies in NR3C1 knock-out rodents, found an exaggerated inflammatory response, aberrant immunomodulation, and immune cell recruitment [8], even linked to transgenerational effects [19] and important reproductive pathologies [53]. Moreover, there is another receptor with a high degree of sequence homology with NR3C1 and a high, but also promiscuous, affinity for glucocorticoid binding, the mineralocorticoid receptor (NR3C2) [54].…”
Section: Discussionmentioning
confidence: 99%
“…This translocation is done with the aid of partner molecules [10,14,15], including the peptidyl-prolyl cis/trans isomerase FK506-binding proteins (FKBP family proteins), which may regulate this translocation [16]. Thus, cortisol-glucocorticoid receptor complexes are responsible for the activation or repression of transcription of target genes (up to 10-20% of the whole genome in humans) [17,18] triggering, in turn, cascades with pleiotropic implications, that include reproductive, immune, and transgenerational effects [8,19].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, maternal stress during pregnancy could dispose of the offspring toward vulnerability to neurobehavioral disorders. As mediators of the stress response, glucocorticoids are among the main primary programming factors conveying maternal stress to the fetus via the placenta (Zarrow et al, 1970;Schmidt et al, 2019), through the activation of the glucocorticoid receptors (GR), whose ontogenetic pattern has been detected in human from the early prenatal life stages (Kitraki et al, 1997;Diaz et al, 1998;Kemp et al, 2016). Thus, glucocorticoids, by a receptor-mediated regulatory role during ontogenic development, could affect normal brain neurogenesis (Cintra et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, last-trimester administration of synthetic glucocorticoids also ''programs'' outcomes comparable to those elicited by prenatal stress in humans (Seckl et al, 2000). Accordingly, treating pregnant rodents with synthetic glucocorticoids leads to offspring with similar HPA axis-and behavioral changes as prenatally stressed offspring (Schmidt et al, 2019).…”
Section: Introductionmentioning
confidence: 99%